Розвиток театральних музеїв на громадських засадах у Лівобережній Україні середини 1950-1980 рр. - Рудавіна, Ірина Геннадіївна (ХДАК, 2012)
Розглянуто розвиток театральних музеїв на громадських засадах у взаємозв’язку з розвитком музейної справи в Україні сер. 1950 — 1980-х рр. Уперше, в культурологічному вимірі, на прикладі музейних закладів Харкова визначено умови і фактори розвитку притеатральних музеїв, розкрито роль особистості в процесі їх створення і діяльності.

The development of theatrical museums on a voluntary basis in an interrelationship with the development of museology in Ukraine from the mid 1950 — 1980 s was considered. Ihe conditions and factors of development of theatrical museums were determined, the role of a personality in the process of their organization and operation was revealed for the first time in an culturological measurement on the pattern of museum s establishments of Kharkiv.
Keywords: музеї театральні; theatrical museums